Odpowiedzi

2010-02-08T20:24:26+01:00
2a - (3a +1) + (a -5)=2a-3a-1+a-5=-6
wyrazenie 2a - (3a +1) + (a -5) jest rowne: -6

-3x(5x-2)=-15x²+6x
2010-02-08T20:25:33+01:00
1. 2a - 3a - 1 + a - 5 =-6
2. -15x² + 6x
3. x razy x = x²
(x+1) razy ( x+1) =x²+x+x+1 = x² + 2x + 1
Pole kwadratu zwiekszylo sie o 2x i 1
Najlepsza Odpowiedź!
2010-02-08T20:27:13+01:00
1. 2a - (3a +1) + (a -5)=2a - 3a -1 +a - 5= -6
2. -3x(5x-2)= -15x² +6x
3.
bok kwadratu= x+1
P= (x+1)²= (x+1)(x+1)= x² + 2x+ 1
A więc pole wzrośnie o 2x+ 1